Essential quality attributes in fresh produce purchase by Malaysian consumers - Hussin, Siti Rahayu; Wong, Foong Yee; Bojei, Jamil (Federal Agricultural Marketing Authority (FAMA), 2010)
Product attribute is one of the most important criteria in consumers’ purchase decision making. This study examines consumers’ perceptions on the essential quality attributes of fresh produce. For this purpose, 1,562 usable responses were analysed. Findings show that quality product attributes such as absence of defect, absence of blemishes, ripeness, freshness, absence of pesticides, absence of preservatives, nutritional value and cleanliness are consistently rated as important for both fruits and vegetables.